A sulfonated covalent organic framework / reduced graphene oxide composite film and a preparation method and application thereof
Patent Information
- Application Number
- CN202511032952.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-07-25
AI Technical Summary
[0006]为此,本发明所要解决的技术问题在于克服现有技术中海水淡化膜存在的低水通量、盐截留率不足、结构稳定性差及易污染等问题
[0036](1)本发明所述的磺化共价有机框架/还原氧化石墨烯复合膜中的磺化共价有机框架材料(磺化COFs)通过接枝磺酸基团引入额外的负电荷,这种负电荷的增加使得复合膜对阳离子具有更高的选择性吸附,同时抑制了阴离子-阳离子的共输运动,进一步提高了盐的排斥率,从而有效提高盐截留率。此外,磺化COFs中的亲水性官能团能够增强水分子与膜之间的氢键作用,这种增强的氢键作用有助于提升水通量。
Smart Images

Figure CN120841645B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of seawater desalination technology, and particularly relates to a sulfonated covalent organic framework / reduced graphene oxide composite membrane, its preparation method and application. Background Technology
[0002] With global population growth and accelerated industrialization, water scarcity has become a key factor restricting social and economic development. The scarcity of freshwater resources, in particular, makes seawater desalination technology a crucial solution to the water crisis. Therefore, developing efficient and economical seawater desalination technologies is of paramount importance. Currently, seawater desalination technologies are mainly divided into two categories: thermal and membrane methods. Among them, membrane technology has received widespread attention due to its advantages such as low energy consumption, ease of operation, and environmental friendliness (Nat.Sustain.2020,3,296 and Sci.Adv.2025,11,eadt3324). Salt separation on membranes can be achieved through pressure-driven membrane-membrane processes (such as reverse osmosis and forward osmosis) or thermal gradient-driven membrane methods (such as membrane distillation and pervaporation). Pervaporation technology uses chemical potential differences to drive water molecules through the membrane, achieving the separation of salt and water. This technology not only effectively overcomes the concentration polarization problem in traditional desalination processes but also utilizes industrial waste heat or renewable energy, reducing energy consumption and improving energy efficiency. However, balancing salt rejection and water flux remains a challenge for the development of existing pervaporation membranes.
[0003] Graphene-based membrane technology has shown great potential due to its excellent chemical stability and mechanical strength. In particular, reduced graphene oxide (rGO) is considered an ideal material for preparing high-efficiency desalination membranes due to its excellent desalination performance and antifouling properties (Chem.Eng.J.2024,483,149108). rGO is a material with high conductivity and high specific surface area obtained by removing oxygen functional groups from graphene oxide (GO) through chemical reduction, restoring the conjugated structure of graphene. rGO membranes not only inherit the excellent properties of graphene, but also exhibit excellent water molecule transport capabilities and selective retention of salt ions due to their nanoscale interlayer spacing and tunable surface chemistry. However, rGO membranes face problems such as low solvent permeability and easy expansion in practical applications, which limit their desalination efficiency and service life.
[0004] Combining rGO with covalent organic frameworks (COFs) presents an innovative solution. COFs are a class of highly ordered porous organic materials that form a stable network structure through covalent bonds. With their highly ordered channels, tunable pore size, and customizable surface functions, COFs can significantly improve membrane permeability and selectivity, as well as enhance hydrophilicity and antifouling capabilities. However, existing rGO / COF composite membranes still cannot achieve a balance between salt rejection and water flux.
[0005] Therefore, there is an urgent need to develop seawater desalination membranes that combine high throughput, high rejection rate, and low energy consumption in order to overcome the aforementioned technical bottlenecks. Summary of the Invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the problems of low water flux, insufficient salt rejection rate, poor structural stability and easy fouling of seawater desalination membranes in the prior art.
[0007] To address the aforementioned technical problems, this invention provides a sulfonated covalent organic framework / reduced graphene oxide (rGO) composite membrane, its preparation method, and its applications. Sulfonated covalent organic framework materials (sulfonated COFs) are introduced into the composite membrane. The presence of negatively charged sulfonic acid groups (-SO3H) significantly enhances the membrane's hydrophilicity, surface roughness, and water permeation rate. Simultaneously, the charge repulsion effect of sulfonated COFs mimics the ion sieving function of fish gills, enhancing the selective retention capacity for salt ions, particularly in high-salt environments. Furthermore, the stable layered structure formed by rGO and sulfonated COFs effectively inhibits membrane expansion, improves mechanical strength, and ensures long-term operational stability. Optimizing the surface topology and hydrophilic functional group distribution of the composite membrane by adjusting the proportion of sulfonated COFs reduces pollutant adhesion, strengthens antifouling performance, and reduces maintenance costs. This biomimetic composite membrane technology achieves a synergistic improvement in water flux, desalination efficiency, durability, and antifouling properties, providing an innovative solution for efficient and economical seawater desalination.
[0008] The first objective of this invention is to provide a sulfonated covalent organic framework / reduced graphene oxide composite membrane, wherein the sulfonated covalent organic framework / reduced graphene oxide composite membrane comprises a base membrane, and a sulfonated covalent organic framework material and a reduced graphene oxide material vacuum-filtered onto the base membrane; the sulfonic acid groups on the surface of the sulfonated covalent organic framework material and the amino groups on the surface of the reduced graphene oxide are bonded by electrostatic attraction.
[0009] The mass ratio of the sulfonated covalent organic framework material to the reduced graphene oxide is (30-50):1.
[0010] In one embodiment of the present invention, the preparation of the sulfonated covalent organic framework material includes the following steps:
[0011] S11. Under the action of a catalyst, trialdehyde phloroglucinol and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine are reacted in a first solvent, and the organic framework material is obtained after washing and drying.
[0012] The organic framework material described in S12 and S11 and the sulfonating agent are reacted in a second solvent, and the sulfonated covalent organic framework material is obtained by centrifugation, washing and drying.
[0013] In one embodiment of the present invention, in S11, the catalyst is acetic acid;
[0014] The first solvent is 1,4-dioxane and trimethylbenzene; the volume ratio of 1,4-dioxane and trimethylbenzene is 1:6.
[0015] The mass ratio of the trialdehyde phloroglucinol, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the catalyst is (20.5-21.5):(35-36):(70-74);
[0016] The reaction temperature is 110℃-130℃, and the time is 64h-80h.
[0017] In one embodiment of the present invention, in S12, the sulfonating agent is 1,3-propanesulfonate lactone;
[0018] The second solvent is toluene;
[0019] The mass ratio of the organic framework material to the sulfonating agent is (14.5-15.5):12000;
[0020] The reaction temperature is 100℃-120℃, and the time is 12h-20h.
[0021] In one embodiment of the present invention, the base film is made of polyvinylidene fluoride.
[0022] A second objective of this invention is to provide a method for preparing the sulfonated covalent organic framework / reduced graphene oxide composite film, comprising the following steps:
[0023] S21. Sulfonated covalent organic framework material and crosslinking agent are added to the reduced graphene oxide dispersion to obtain a mixture;
[0024] S22. Vacuum filter the mixture described in S21 onto the base membrane to obtain a composite membrane;
[0025] S23. The composite membrane described in S22 is immersed in an acyl chloride reagent solution to carry out an interfacial polymerization reaction, and after curing and washing, the sulfonated covalent organic framework / reduced graphene oxide composite membrane is obtained.
[0026] In one embodiment of the present invention, in S21, the crosslinking agent is selected from m-phenylenediamine and / or p-phenylenediamine;
[0027] The concentration of the reduced graphene oxide dispersion is 0.04 mg / mL to 0.067 mg / mL;
[0028] The mass ratio of the sulfonated covalent organic framework material to the reduced graphene oxide is (30-50):1;
[0029] The mass ratio of the sulfonated covalent organic framework material to the crosslinking agent is 8:(99-101).
[0030] In one embodiment of the present invention, in S22, the vacuum degree of the vacuum filtration is -0.09MPa to -0.11MPa.
[0031] In one embodiment of the present invention, in S23, the acyl chloride reagent is pyromellitic trimethylolpropionate chloride;
[0032] The concentration of the acyl chloride reagent solution is 0.09 w / v%-0.11 w / v, and the solvent is n-hexane;
[0033] The interfacial polymerization reaction is carried out at a temperature of 15℃-35℃ for a time of 1min-3min.
[0034] A third objective of this invention is to provide an application of the aforementioned sulfonated covalent organic framework / reduced graphene oxide composite membrane in seawater desalination.
[0035] The technical solution of the present invention has the following advantages compared with the prior art:
[0036] (1) The sulfonated covalent organic framework material (sulfonated COFs) in the sulfonated covalent organic framework / reduced graphene oxide composite membrane of the present invention introduces additional negative charges through grafting sulfonic acid groups. This increase in negative charge makes the composite membrane more selective for cation adsorption, while inhibiting the co-transport of anions and cations, further improving the salt rejection rate, thereby effectively improving the salt rejection rate. In addition, the hydrophilic functional groups in the sulfonated COFs can enhance the hydrogen bonding between water molecules and the membrane, and this enhanced hydrogen bonding helps to improve water flux.
[0037] (2) The sulfonated covalent organic framework / reduced graphene oxide composite membrane of the present invention increases the roughness of the composite membrane by sulfonating COFs. The increase in roughness can increase water flux through the synergistic effect of multiple mechanisms: on the one hand, the micro-uneven structure can increase the hydrophilic contact area between the membrane surface and water molecules, and reduce mass transfer resistance; on the other hand, the physical scouring effect of the rough surface can inhibit the deposition of pollutants and disperse the clogging sites, thereby alleviating membrane fouling; at the same time, its disturbance to the boundary layer can reduce concentration polarization and optimize the transmembrane pressure distribution.
[0038] (3) The sulfonated covalent organic framework / reduced graphene oxide composite membrane of the present invention combines rGO with sulfonated COFs. On the one hand, the high mechanical strength of rGO provides good stability and durability for the composite membrane, while the ordered pore structure and hydrophilic functional groups of sulfonated COFs provide excellent separation performance. On the other hand, the combination of rGO and sulfonated COFs can form a robust layered structure, which further improves the stability and durability of the composite membrane. Therefore, this composite membrane can not only shorten the solvent transport path and improve the permeation efficiency, but also enhance the long-term operational stability of the membrane while maintaining a high desalination rate. This is of great significance for improving the practicality and economy of the composite membrane.
[0039] (4) The preparation method of the present invention prepares a composite membrane by combining vacuum filtration and interfacial polymerization. The rGO-STaTp heterolayer is oriented and assembled by vacuum filtration to simulate the nanofluid channels between gill filaments. The sulfonic acid groups enriched on the surface of STaTp are used to construct a charge repulsion interface to reproduce the ion sieving effect of gill filament epidermal cells. Furthermore, the surface topology of the composite membrane is controlled by interfacial polymerization technology to form a hydrophilic rough structure similar to gill filament microprotrusions to enhance the driving force of water molecule penetration. In addition, interfacial polymerization can cause the surface of the composite membrane to undergo interfacial polymerization reaction between acyl chloride and amino groups, thus avoiding the generation of membrane defects.
[0040] (5) The sulfonated covalent organic framework / reduced graphene oxide composite membrane described in this invention can be applied to water treatment fields such as seawater desalination and brackish water desalination. Due to its good adaptability in saline solutions of different concentrations, it has broad application prospects and can effectively solve the problem of water shortage. Attached Figure Description
[0041] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein:
[0042] Figure 1 This is a schematic diagram of the synthesis route of the sulfonated covalent organic framework / reduced graphene oxide composite film in Example 1 of the present invention;
[0043] Figure 2The following are the characterization results of STaTp@rGO composite membranes prepared with different amounts of STaTp in Test Example 1 of the present invention; wherein, (a) is the SEM image of the surface of the rGO membrane (without STaTp), (b) is the SEM image of the surface of the STaTp@rGO-10 composite membrane, (c) is the SEM image of the surface of the STaTp@rGO-20 composite membrane, (d) is the SEM image of the surface of the STaTp@rGO-30 composite membrane, (e) is the SEM image of the surface of the STaTp@rGO-40 composite membrane, (f) is the SEM image of the surface of the STaTp@rGO-50 composite membrane, (g) is the AFM image of the rGO membrane, and (h) is the AFM image of the STaTp@rGO-40 composite membrane;
[0044] Figure 3 The contact angle test results are for STaTp@rGO composite films prepared with different contents of STaTp in Test Example 2 of this invention.
[0045] Figure 4 This is the testing apparatus for the desalination performance in Test Example 3 of the present invention;
[0046] Figure 5 The desalination performance test results of STaTp@rGO composite membranes prepared with different contents of STaTp in Test Example 3 of the present invention;
[0047] Figure 6 The results of long-term stability testing of the STaTp@rGO-40 composite membrane in Test Example 4 of this invention are shown. Detailed Implementation
[0048] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0049] In this invention, unless otherwise stated, the PVDF membrane used in the embodiments of this invention was purchased from Suzhou Suke Precision Instruments Co., Ltd., and has a pore size of 0.1μm and a diameter of 47mm.
[0050] Example 1
[0051] Reference Figure 1 As shown, the sulfonated covalent organic framework / reduced graphene oxide composite film and its preparation method in this embodiment specifically include the following steps:
[0052] S1. Preparation of reduced graphene oxide (rGO) dispersion: Graphene oxide (GO) nanosheets were ultrasonically dispersed in ultrapure water to form a GO dispersion with a concentration of 0.05 mg / mL; 50 mL of GO dispersion was placed in a 100 mL reaction vessel, and 100 μL of ammonia solution (25 wt%) and 20 μL of hydrazine hydrate solution (80 wt%) were added. The mixture was reacted at 90 °C for 2 h to obtain an rGO dispersion with a concentration of 0.05 mg / mL.
[0053] S2, Preparation of sulfonated covalent organic framework material (STaTp):
[0054] S21. Preparation of covalent organic framework material (COF-TaTp): 21 mg of trialdehyde phloroglucinol, 35.4 mg of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 2.4 mL of a 1,4-dioxane / trimethylbenzene (volume ratio 1:6) mixed solvent were added to a 20 mL ampoule and sonicated for 10 min. Then, 0.4 mL of acetic acid (3 mol / L) was added and sonicated for another 30 min. The mixture was degassed by a three-stage freeze-thaw cycle, vacuum sealed, and heated at 120 °C for 3 days. The mixture was then washed sequentially with 1,4-dioxane, tetrahydrofuran, and acetone, and then vacuum dried at 100 °C to obtain COF-TaTp.
[0055] S22. Preparation of sulfonated covalent organic framework material (STaTp): 15 mg COF-TaTp and 10 mL 1,3-propanesulfonate lactone were added to a 50 mL flask containing 20 mL toluene and stirred until homogeneous. The mixture was refluxed at 110 °C for 16 h. After the reaction was complete, the solid was collected by centrifugation and washed successively with ethanol, 1,4-dioxane, NaOH aqueous solution (pH = 10), deionized water and anhydrous acetone. The solid was then dried under vacuum at 100 °C to obtain STaTp.
[0056] S3. Preparation of reduced graphene oxide (STaTp@rGO) composite membrane modified with covalent organic framework material: 4 mL of rGO dispersion (0.05 mg / mL), 8 mg of STaTp and 5 mL of m-phenylenediamine aqueous solution (2.0 wt%) were mixed evenly, and the volume was adjusted to 50 mL with water. The mixture was then sonicated to obtain a mixture. 5 mL of the mixture was vacuum filtered onto a PVDF membrane at -0.1 MPa. The membrane was then immersed in a hexane solution of trimesoyl chloride (0.1 w / v%) at room temperature for 2 min, cured in an oven at 80 °C for 10 min, and rinsed with deionized water to obtain the STaTp@rGO-40 composite membrane.
[0057] Test Example 1
[0058] Based on Example 1, the effect of different contents of STaTp (the mass ratio of STaTp to rGO, x, were 0, 10, 20, 30, 40, and 50, respectively) on the microstructure of the STaTp@rGO composite membrane was investigated. The characterization results are as follows: Figure 2 As shown. From Figure 2 It can be seen that the rGO membrane surface is relatively flat with a micro-wrinkled structure; after adding STaTp, the STaTp@rGO composite membrane surface shows obvious undulating wrinkles, and the wrinkles become more pronounced with increasing STaTp content. In addition, the surface roughness of the STaTp@rGO composite membrane is significantly increased compared to the rGO membrane, which is beneficial for increasing the contact area with water molecules.
[0059] Test Example 2
[0060] Based on Test Example 1, contact angle tests were conducted on STaTp@rGO composite membranes prepared with different amounts of STaTp, and the results are as follows: Figure 3 As shown. From Figure 3 It can be seen that STaTp can reduce the water contact angle of the prepared STaTp@rGO composite membrane, thereby improving water permeability. Furthermore, the hydrophilicity of the STaTp@rGO composite membrane increases with increasing STaTp content.
[0061] Test Example 3
[0062] use Figure 4 The apparatus was used to test the desalination performance of STaTp@rGO composite membranes prepared with different STaTp contents. A peristaltic pump (100 rpm) on the feed side continuously circulated the feed liquid. A vacuum pump maintained the permeation under vacuum. Vacuum vapor was measured by condensing the permeate in a cold trap. The water flux was calculated by weighing the liquid collected in the cold trap, and the salt rejection rate was calculated by measuring the conductivity of the liquid in the cold trap using a conductivity meter. The effective area of the STaTp@rGO composite membrane was 6.15 cm². 2 The formula for calculating the membrane flux of the STaTp@rGO composite membrane is J=ΔM / (A×Δt); where J is the membrane flux (kg / (m³)). 2 ·h)), ΔM is the mass of the permeate (kg), and A is the effective area (m²). 2 ), Δt is the test time (h); the desalination rate (R) is calculated using the formula R = (1 - C) / (h). t / C0); where C t C0 is the permeate concentration (salt concentration in the permeate), and C0 is the feed concentration (salt concentration in the feed solution); the results are as follows Figure 5 As shown. From Figure 5It can be seen that with the increase of STaTp content, the permeation flux and removal rate of the STaTp@rGO composite membrane increase. Among them, the STaTp@rGO-40 composite membrane has the best permeation flux, exhibiting an ultra-high flux (53.44 kg / (m³)) in the NaCl (3.5 wt%) system. 2 The high salt rejection rate (99.91%) is due to the presence of strong hydrophilic sulfonic acid groups in STaTp, which enhance the hydrophilicity of the membrane surface with increasing content, thereby reducing diffusion resistance by enhancing hydrogen bonding of water molecules. Its negative charge creates a charge repulsion effect, which, combined with electrostatic recombination with the rGO layer, stabilizes the interlayer spacing and regulates the charge state, improving the salt rejection rate through ion sieving. Simultaneously, STaTp introduces increased membrane surface roughness and micro / nano-folded structures, expanding the water contact area and inhibiting pollutant adhesion, thus optimizing mass transfer efficiency.
[0063] Test Example 4
[0064] Based on Test Example 3, a long-term stability test was conducted on the STaTp@rGO-40 composite membrane of Example 1, and the results are as follows. Figure 6 As shown. From Figure 6 It can be seen that during 100 hours of continuous operation, the permeation flux of the STaTp@rGO-40 composite membrane decreased by less than 10%, and the NaCl rejection rate remained above 99%, indicating that the STaTp@rGO-40 composite membrane has good stability. This is because the covalent network structure of STaTp endows the composite membrane with excellent chemical stability, resisting physicochemical erosion during long-term operation; the electrostatic recombination of rGO and STaTp forms a stable layered structure, the high mechanical strength of rGO inhibits membrane expansion or rupture, while the ordered channels of STaTp maintain unobstructed mass transfer pathways; at the same time, the presence of a dense interface layer reduces structural defects, ensuring long-term stable separation performance.
[0065] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. The application of a sulfonated covalent organic framework / reduced graphene oxide composite membrane in seawater desalination, characterized in that, The sulfonated covalent organic framework / reduced graphene oxide composite membrane includes a base membrane, and sulfonated covalent organic framework material and reduced graphene oxide vacuum-filtered onto the base membrane; the sulfonic acid groups on the surface of the sulfonated covalent organic framework material and the amino groups on the surface of the reduced graphene oxide are bonded by electrostatic attraction. The mass ratio of the sulfonated covalent organic framework material to the reduced graphene oxide is (30-50):1; The preparation of the sulfonated covalent organic framework material includes the following steps: S11. Under the action of a catalyst, trialdehyde phloroglucinol and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine are reacted in a first solvent, and the organic framework material is obtained after washing and drying. The organic framework material described in S12 and S11 and the sulfonating agent are reacted in a second solvent, and the sulfonated covalent organic framework material is obtained by centrifugation, washing and drying; the sulfonating agent is 1,3-propanesulfonate lactone. The method for preparing the sulfonated covalent organic framework / reduced graphene oxide composite film, Includes the following steps: S21. Sulfonated covalent organic framework material and crosslinking agent are added to the reduced graphene oxide dispersion to obtain a mixture; the crosslinking agent is selected from m-phenylenediamine and / or p-phenylenediamine; S22. Vacuum filter the mixture described in S21 onto the base membrane to obtain a composite membrane; S23. The composite membrane described in S22 is immersed in an acyl chloride reagent solution to carry out an interfacial polymerization reaction, and after curing and washing, the sulfonated covalent organic framework / reduced graphene oxide composite membrane is obtained.
2. The application according to claim 1, characterized in that, In S11, the catalyst is acetic acid; The first solvent is 1,4-dioxane and trimethylbenzene; the volume ratio of 1,4-dioxane and trimethylbenzene is 1:
6. The reaction temperature is 110℃-130℃, and the time is 64h-80h.
3. The application according to claim 1, characterized in that, In S12, the second solvent is toluene; The reaction temperature is 100℃-120℃, and the time is 12h-20h.
4. The application according to claim 1, characterized in that, The base membrane is made of polyvinylidene fluoride.
5. The application according to claim 1, characterized in that, In S21, the concentration of the reduced graphene oxide dispersion is 0.04 mg / mL to 0.067 mg / mL.
6. The application according to claim 1, characterized in that, In S23, the acyl chloride reagent is pyromellitic acid chloride; The concentration of the acyl chloride reagent solution is 0.09 w / v%-0.11 w / v, and the solvent is n-hexane; The interfacial polymerization reaction is carried out at a temperature of 15℃-35℃ for a time of 1min-3min.